2019
DOI: 10.1021/acs.jmedchem.8b01573
|View full text |Cite
|
Sign up to set email alerts
|

Structural Basis of Altered Potency and Efficacy Displayed by a Major in Vivo Metabolite of the Antidiabetic PPARγ Drug Pioglitazone

Abstract: Pioglitazone (Pio) is an FDA-approved drug for type 2 diabetes that binds and activates the nuclear receptor PPARγ. yet it remains unclear how in vivo Pio metabolites affect PPARγ structure and function. Here, we present a structure-function comparison of Pio and its most abundant in vivo metabolite, 1-hydroxypioglitazone (PioOH). PioOH displayed a lower binding affinity and reduced potency in coregulator recruitment assays. X-ray crystallography and molecular docking analysis of PioOH-bound PPARγ ligand-bindi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 69 publications
0
13
0
Order By: Relevance
“…By TR-FRET analysis, it was confirmed that the PPARγ partial agonist F12016 had a lower recruiting ability to coactivators than the PPARγ complete agonist and reduced the side effect of bone loss ( Liu et al, 2015 ). Other partial agonists, telmisartan, FMOC-L-Leu and PA-082, for instance, also showed a decrease in side effects, such as adipogenesis and weight gain, possibly due to differences in recruiting different coactivators ( Burgermeister et al, 2006 ; Liu et al, 2015 ; Li et al, 2016 ; Mosure et al, 2019 ; Ribeiro Filho et al, 2019 ). These studies have implications for our study in that the different effects of CMHX008 and rosiglitazone on cardiomyocytes may be caused by the recruitment of different coactivators.…”
Section: Discussionmentioning
confidence: 99%
“…By TR-FRET analysis, it was confirmed that the PPARγ partial agonist F12016 had a lower recruiting ability to coactivators than the PPARγ complete agonist and reduced the side effect of bone loss ( Liu et al, 2015 ). Other partial agonists, telmisartan, FMOC-L-Leu and PA-082, for instance, also showed a decrease in side effects, such as adipogenesis and weight gain, possibly due to differences in recruiting different coactivators ( Burgermeister et al, 2006 ; Liu et al, 2015 ; Li et al, 2016 ; Mosure et al, 2019 ; Ribeiro Filho et al, 2019 ). These studies have implications for our study in that the different effects of CMHX008 and rosiglitazone on cardiomyocytes may be caused by the recruitment of different coactivators.…”
Section: Discussionmentioning
confidence: 99%
“…Other ligand-bound PPARγ LBD crystal structures obtained from soaking ligand into apo-protein crystals have similarly revealed a ligand bound to this pocket entrance in chain B molecules ( Fig. S4) (24,37,(46)(47)(48)(49)(50)(51), including a crystal structure we previously solved of darglitazone-bound PPARγ LBD (Fig. 4C).…”
Section: Crystal Structures Reveal the Putative Ligand Entry Site To mentioning
confidence: 67%
“…To evaluate the potential of pioglitazone; a thiazolidinedione compound, to produce anxiety like behavior in rodents, present study was designed. Gain in weight, breathlessness and ankle swelling are manifested due to the retention of fluid by administration of thiazolidinedione compounds (Nanjan et al, 2018). However, there is no documentation of changes in behavioral activities or alterations in central nervous system (CNS).…”
Section: Discussionmentioning
confidence: 99%
“…Nuclear receptor peroxisome proliferator-activated receptor gamma (PPAR-gamma) are selectively stimulated by pioglitazone. Regulation of the genes transcription which are insulin-responsive by the activation of these PPAR-gamma receptors is achieved, which in turn controls utilization, production and transport of glucose (Mosure et al, 2019;Seok et al, 2019).…”
Section: Introductionmentioning
confidence: 99%